(untitled) (Philological Studies, 2019)
In the work we deal with the problematic transposition of Nietzschean concepts of dance, elevation and historical memory in the works written by two authors from different national traditions: Kraljevo written by the Croatian author Miroslav Krleža, and Horo written by the Bulgarian author Anton Strašimirov. In both works the authors deal with problems of a specific cultural and national crisis. Horo is a grotesque representation of the historical events connected with the September Uprising which, as a civil war, represents a crisis of the stable national identity. The disintegration of the national unity results in the distortion of the linear temporal continuity incarnated in the image of a family genealogy, followed by the loss of the fundamental precondition for a stable ethical system - memory. Kraljevo also deals with a specific historical and national crisis in the middle of the World War I. In both works, the dance ends not with an elevation, but with a declination. Such scenes represent a symbolic return to the mother earth. In both works the sign of the women and femininity as a cultural Other is connected to the representation of the mortality of men and a false promise of its overcoming